TREATMENT METHODS FOR OBESITY IN ADULTS: ADVANTAGES AND DISADVANTAGES – LITERATURE REVIEW - Dominika Karolak; Tymoteusz Białowąs; Natalia Sara Kuśmierowska; Monika Kuś; Grzegorz Słomkowski; Kacper Cholewiński; Daria Valipur Kolti; Milena Polak; Magdalena Natalia Nowak; Konrad Wiśniewski (International Journal of Innovative Technologies in Social Science, 2026)
Background: Obesity is a growing public health crisis requiring timely intervention to prevent severe comorbidities (e.g., cardiovascular disease, type 2 diabetes) and improve patient survival. Aim: To evaluate current obesity therapies—lifestyle modifications, pharmacotherapy, bariatric surgery, and experimental methods (FMT, DBS)—comparing their efficacy, complications, and required patient effort. Materials and Methods: A targeted PubMed literature review using keywords such as "obesity treatment" and "bariatric surgery." Results: Obesity has a multifactorial etiology. Lifestyle modifications are foundational but typically yield a modest weight loss of 5-10% and are limited by counter-regulatory mechanisms. Pharmacotherapy (e.g., GLP-1 receptor agonists) provides significant reduction ( 20%), whereas bariatric surgery remains the most effective intervention for substantial, sustained weight loss and comorbidity remission. Conclusion: Standalone lifestyle interventions are often insufficient due to high weight regain rates. Optimal long-term clinical outcomes require an individualized, integrated approach combining permanent behavioral changes with appropriate pharmacological or surgical therapies.